Biosynthesis of the [FeFe] hydrogenase H-cluster via a synthetic [Fe(ii)(CN)(CO)2(cysteinate)]− complex. Issue 36 (26th August 2021) - Britt, R. David; Rauchfuss, Thomas B.
Abstract : The synthetic complex [Fe(ii )(CN)(CO)2 (cysteinate)] − as donated from Syn-B bound as the substrate in the radical SAM enzyme HydE. Abstract : The H-cluster of [Fe–Fe] hydrogenase consists of a [4Fe] H subcluster linked by the sulfur of a cysteine residue to an organometallic [2Fe] H subcluster that utilizes terminal CO and CN ligands to each Fe along with a bridging CO and a bridging SCH2 NHCH2 S azadithiolate (adt) to catalyze proton reduction or hydrogen oxidation. Three Fe–S "maturase" proteins, HydE, HydF, and HydG, are responsible for the biosynthesis of the [2Fe] H subcluster and its incorporation into the hydrogenase enzyme to form this catalytically active H-cluster. We have proposed that HydG is a bifunctional enzyme that uses S -adenosylmethione (SAM) bound to a [4Fe–4S] cluster to lyse tyrosine via a transient 5′-deoxyadenosyl radical to produce CO and CN ligands to a unique cysteine-chelated Fe(ii ) that is linked to a second [4Fe–4S] cluster via the cysteine sulfur. In this "synthon model", after two cycles of tyrosine lysis, the product of HydG is completed: a [Fe(CN)(CO)2 (cysteinate)] − organometallic unit that is vectored directly into the synthesis of the [2Fe] H sub-cluster. However our HydG-centric synthon model is not universally accepted, so further validation is important. In this Frontiers article, we discuss recent results using a synthetic "Syn-B" complex that donates [Fe(CN)(CO)2 (cysteinate)] − units that match our proposed HydG product. Can Syn-B activate hydrogenase in the absence of HydG and its tyrosine substrate? If so, since Syn-B can be synthesized with specific magnetic nuclear isotopes and with chemical substitutions, its use could allow its enzymatic conversions on the route to the H-cluster to be monitored and modeled in fresh detail.